Rancangan Optimasi Proses Blending Batubara Di PT Binuang Mitra Blok Dua, Kecamatan Binuang, Kabupaten Tapin, Kalimantan Selatan - Anin, Michell Satria Chame; Haq, Shofa Rijalul; Probowati, Dyah; Ernawati, Rika (Universitas Pembangunan Nasional Veteran Yogyakarta, 2025)
PT Binuang Mitra Bersama Blok Dua (PT BMBBD) operates in the coal mining industry with a focus on blending coal to meet market specifications. The main challenge faced by the company is maintaining the consistency of the coal's calorific value, targeted between 4000-4200 Kcal/kg. Variations in coal quality resulting from different seams, along with an optimal blending process not yet in place, lead to discrepancies between production results and the set standards. This research aims to analyze the suitability of the calorific value of PT BMBBD's coal in line with marketing targets, evaluate the effectiveness of the blending process implemented, and optimize the mixing of coal to achieve more consistent results that align with market specifications. The data used in this study includes primary data from field sampling and laboratory tests, as well as secondary data obtained from coal quality reports and internal company information. Data analysis is conducted using proximate analysis methods according to ASTM standards, along with optimization of the blending process using Microsoft Excel's Solver. The research results indicate that there is a discrepancy between the coal quality produced and the calorific value targets set by the company. Some seams produce coal with lower quality than the expected standards, highlighting the need for blending process optimization. By applying optimization methods, the results of the coal blending can be better aligned with market needs, thereby improving the consistency of calorific values and production efficiency. This study provides significant contributions to the operational improvement of PT BMBBD, particularly in efforts to enhance coal quality and consistency. The findings are expected to serve as a reference for the company in optimizing the blending process and managing coal quality more effectively in accordance with market demands.